2001
DOI: 10.2466/pms.2001.92.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in Sport: An Achievement Goal Perspective in Young Spanish Recreational Athletes

Abstract: This study examined the relationship between goal orientations, perceived motivational climate, enjoyment, satisfaction, perception of ability, and preference for tasks with different levels of difficulty in Spanish athletes. To measure these variables 323 recreational athletes completed the Spanish versions of the Perception of Success Questionnaire, Perception of Significant Others' Sport Success Criteria Questionnaire, Enjoyment/Boredom scale, and Satisfaction in Sport Questionnaire. To measure perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
3
14
0
4
Order By: Relevance
“…The replies are rated on a Likerttype scale, in which each item has a response range from 1 to 100 (anchors: 0 = strongly disagree and 10 = strongly agree). The Spanish version of this questionnaire showed a factor distribution and internal consistency coefficients similar to those obtained for American athletes and physical education students [28,29]. Likewise, the inventory for this study showed adequate internal consistency for each subscale, with Cronbach alpha coefficients from .93 for the ego orientation subscale and .87 for the task orientation subscale.…”
Section: Perception Of Success Questionnaire (Posq)supporting
confidence: 75%
See 1 more Smart Citation
“…The replies are rated on a Likerttype scale, in which each item has a response range from 1 to 100 (anchors: 0 = strongly disagree and 10 = strongly agree). The Spanish version of this questionnaire showed a factor distribution and internal consistency coefficients similar to those obtained for American athletes and physical education students [28,29]. Likewise, the inventory for this study showed adequate internal consistency for each subscale, with Cronbach alpha coefficients from .93 for the ego orientation subscale and .87 for the task orientation subscale.…”
Section: Perception Of Success Questionnaire (Posq)supporting
confidence: 75%
“…To measure students' dispositional goal orientation in physical education classes, the Spanish version [27][28][29]. This questionnaire has 12 items, of which six measure task orientation (e.g.…”
Section: Perception Of Success Questionnaire (Posq)mentioning
confidence: 99%
“…Extensive research has shown the attachment with prosperity, joy, task insistency, adaptability (Ntoumanis & Biddle, 1999;Roberts, 2012;Van De Pol, Kavussanu, & Ring, 2012), greater efforts, pleasure, decreased anxiety (Cunningham & Xiang, 2008;Kavussanu & Roberts, 2001;Atkins, Johnson, Force, & Petrie, 2015;, self-evaluation and general satisfaction (Kavussanu & Harnisch, 2000;Le Bars, Gernigon, & Ninot, 2009;Atkins et al, 2015). In a performance motivational climate instructors encourage social comparison, superficially stimulate students during learning process using on regulative evaluation and recompensing performance results (Ames, 1992;Ames & Archer, 1988;Murcia, Camacho, & Rodríguez, 2008;Keegan, Spray, Harwood, & Lavallee, 2010), and enhance thereby the competition among students complimenting the most talented students (Cervelló & Santos-Rosa, 2001;Nicholls, 1989;). Performance-related motivational climate induces feelings of anxiety, stress, confusion, boredom and withdrawal, as it prevails lack of motivation (Liukkonen, Barkoukis, Watt, & Jaakkola, 2010;Braithwaite, Spray, & Warburton, 2011;Cumming, Smoll, Smith, & Grossbard, 2007;Nerstad, Roberts, & Richardsen, 2013;Van De Pol et al, 2012;Granero-Gallegos et al, 2014;Ommundsen & KvalØ, 2007).…”
Section: Motivational Climatementioning
confidence: 99%
“…Görev, ego ve sosyal güdüler motivasyon üzerinde ayrıca rol oynarlar (12,18). Görev güdüsü içseldir ve bir katılımcı aktiviteye zevk ve kişisel ödül için girmeye karar verdiğinde ortaya çıkar (12).…”
Section: Gi̇ri̇ş Ve Amaçunclassified